2005
DOI: 10.1002/ijc.21385
|View full text |Cite
|
Sign up to set email alerts
|

Detailed assessment of chromosome 22 aberrations in sporadic pheochromocytoma using array‐CGH

Abstract: Pheochromocytoma is a predominantly sporadic neuroendocrine tumor derived from the adrenal medulla. Previous low resolution LOH and metaphase-CGH studies reported the loss of chromosomes 1p, 3q, 17p and 22q at various frequencies. However, the molecular mechanism(s) behind development of sporadic pheochromocytoma remains largely unknown. We have applied highresolution tiling-path microarray-CGH with the primary aim to characterize copy number imbalances affecting chromosome 22 in 66 sporadic pheochromocytomas.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…Jarbo et al (2005) reported that the ratios of chromosome 22q loss in some PCC samples were higher than expected for a single allele ratio, and suggested this could be due to intra-tumoral heterogeneity. Diaz-Cano et al (2000) investigated heterogeneity of sporadic and MEN 2-related PCC and adrenal medullary hyperplasia (AMH) nodules, by determining the methylation patterns of the androgen receptor (AR) gene, localized on the X-chromosome.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Jarbo et al (2005) reported that the ratios of chromosome 22q loss in some PCC samples were higher than expected for a single allele ratio, and suggested this could be due to intra-tumoral heterogeneity. Diaz-Cano et al (2000) investigated heterogeneity of sporadic and MEN 2-related PCC and adrenal medullary hyperplasia (AMH) nodules, by determining the methylation patterns of the androgen receptor (AR) gene, localized on the X-chromosome.…”
Section: Introductionmentioning
confidence: 96%
“…While loss of chromosome 1p is the most common genetic aberration reported in sporadic PCC (Dannenberg et al 2000, Edstrom et al 2000, Cascon et al 2005), particular genetic alterations have been demonstrated in syndrome-related PCC (Edstrom et al 2000, Lui et al 2002, Jarbo et al 2005. Generally, MEN 2-related PCCs show loss of chromosomes 1p and 3q (Edstrom et al 2000, Jarbo et al 2005, SDHD-related PCCs and PGLs display loss of chromosome 11 (Hensen et al 2004), and in NF1-related tumors, frequent loss of 1p and 17q is found (Edstrom et al 2000, Bausch et al 2007.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique has facilitated the analysis of chromosomes 21 and 22 that were difficult to analyze in conventional CGH. Recently, copy number imbalances affecting chromosome 22 were confirmed by submegabase array-CGH in 44% (29/66) of PCC analyzed, a percentage that had not been described in conventional CGH (Jarbo et al 2006). In addition, the tiling order of bacterial artificial chromosome (BAC) clones also has the advantage to rule out mismapped clones, and gives precise breakpoint information.…”
Section: Introductionmentioning
confidence: 99%
“…Loss of heterozygosity (LOH) and comparative genomic hybridization (CGH) studies performed by us and others have reported allelic losses at 1p, 3pq, 17p, and 22q, but corresponding genes have not been identified. [3][4][5][6] Particularly 17p, the chromosome arm where the p53 gene is located, is interesting to investigate knowing that aberrations in this gene are implicated in many inherited and sporadic forms of malignancy, such as colon, lung, brain, and breast tumors. 7 p53 is functionally involved in guarding the stability of the genome.…”
mentioning
confidence: 99%